Dielectric characterization of bentonite clay at various moisture contents and with mixtures of biomass in the microwave spectrum. Issue 1 (2nd January 2018) - Ellison, Candice; McKeown, Murat Sean; Trabelsi, Samir; Marculescu, Cosmin; Boldor, Dorin
ABSTRACT: This study assesses the potential for using bentonite as a microwave absorber for microwave-assisted biomass pyrolysis based on the dielectric properties. As bentonite is a hygroscopic material, the effect of bound water content on dielectric properties was addressed in this study. Dielectric properties of bentonite at different moisture contents were measured using a coaxial line dielectric probe and vector network analyser in the microwave frequency range from 0.2 to 4.5 GHz at room temperature. Further, dielectric properties of mixtures of bentonite with biomass were measured from 1.5 to 20 GHz as mixtures of bentonite with biomass could have microwave processing applications such as the thermochemical conversion of biomass to biofuel. Both dielectric constant and dielectric loss factor increased linearly with increasing moisture content. Measurements on biomass and bentonite mixtures show a quadratic increase in dielectric constant and loss factor with increasing bentonite content and with moisture contents ranging from 9.5% (pure bentonite) to 11.4% (pure biomass) wet basis. At 915 MHz, dielectric constant ranged from 2.0 to 6.2 and dielectric loss ranged from 0.2 to 2.7, respectively. At 2450 MHz, dielectric constant ranged from 1.8 to 5.1 and dielectric loss ranged from 0.7 to 2.6, respectively.